2013
DOI: 10.1371/journal.pone.0055677
|View full text |Cite
|
Sign up to set email alerts
|

Origin of African Physacanthus (Acanthaceae) via Wide Hybridization

Abstract: Gene flow between closely related species is a frequent phenomenon that is known to play important roles in organismal evolution. Less clear, however, is the importance of hybridization between distant relatives. We present molecular and morphological evidence that support origin of the plant genus Physacanthus via “wide hybridization” between members of two distantly related lineages in the large family Acanthaceae. These two lineages are well characterized by very different morphologies yet, remarkably, Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…bees, flies, butterflies, and hummingbirds), and some of these have been shown to be at least partially interfertile in Carlowrightia (Daniel, 1983a), Anisacanthus (Daniel, 1985), and Tetramerium (Daniel, 1986). Although hybrids were not identified in natural populations of Schaueria and Thyrsacanthus species, older interspecific hybridization events could be involved in the diversification of the two lineages, as recognized in other plant groups (Fehrer et al, 2007; Palma‐Silva et al, 2011; Jabaily and Sytsma, 2013), as well as in Acanthaceae (Tripp et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…bees, flies, butterflies, and hummingbirds), and some of these have been shown to be at least partially interfertile in Carlowrightia (Daniel, 1983a), Anisacanthus (Daniel, 1985), and Tetramerium (Daniel, 1986). Although hybrids were not identified in natural populations of Schaueria and Thyrsacanthus species, older interspecific hybridization events could be involved in the diversification of the two lineages, as recognized in other plant groups (Fehrer et al, 2007; Palma‐Silva et al, 2011; Jabaily and Sytsma, 2013), as well as in Acanthaceae (Tripp et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Brysting et al, 2007;Kim et al, 2008;Mason-Gamer, 2008;Grusz et al, 2009;Ishikawa et al, 2009;Nitta et al, 2011;Dyer et al, 2012;Sessa et al, 2012;Metzgar et al, 2013;Sigel et al, 2014). In addition, such low-copy nuclear data are useful for investigating questions unrelated to polyploidy, such as 'classical' nonpolyploid phylogenetic inference (Zhang et al, 2012), inference of hybridization (Govindarajulu et al, 2011;Tripp et al, 2013;Rothfels et al, 2015), horizontal gene transfer (Li et al, 2014), and studies of gene family and genome evolution (Popp & Oxelman, 2004;Rauscher et al, 2004;Flagel & Wendel, 2009;Weiss-Schneeweiss et al, 2011;Larsen et al, 2014;Li et al, 2015). In particular, this approach allows researchers to easily sequence both alleles for heterozygous accessions (of any ploidy level), providing highly informative dominant markers for coalescent-based analyses or inferences of Table 3); color curves show the smoothed fits for each of the analysis regimes a, b and c. New Phytologist population structure.…”
Section: Single-molecule Amplicon Sequencing Of Polyploidsmentioning
confidence: 99%
“…This phenomenon in the breeding parents of cypress was also observed in other annual and perennial plants, such as sorghum and poplar [49,50], suggesting that there was no obvious differentiation in the population structure of cypress from different geographic origins. The relationship and geographic origin of the parents play an important role in maintaining a high level of genetic diversity and the generation of heterotic progenies through crossbreeding [51,52]. The analysis based on the Mantel test (Figure 2) showed that the genetic distance was not correlated with the geographic distance (r = 0.02 and p = 0.530), suggesting that the geographic distance is not the principal factor influencing genetic differentiation among the breeding parents of cypress.…”
Section: Discussionmentioning
confidence: 99%